TREND THE GLOBALIZATION OF THE GLOBALIZATION PROOF OF THE CONSTITUTIONAL CONSTITUTION OF LOCAL WISDOM AND THE CONFLICT RESOLUTION IN THE COMMUNITY - Zuhroh, Ni’matuz (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The trend of global culture is a product of western culture spread throughout the world through the advantages of electronic technology and various forms of media and communication systems. The global community is given the prestige of dispensation in prestige and hegemony in information. Globalization has minimized protection in the local culture through the process of liberalization (privatization) of markets and widespread trade in many developing countries, the distribution of western cultural products such as films, literature, lifestyles, new values and so on. Has polluted the local culture so that the rise of domestic violence, juvenile delinquency, broken home. Modernization or globalization affects the family life there are at least two; First concentration of family members, especially husband and wife, focuses solely on pleasure in marriage life rather than thinking about responsibility. some married couples if they agree to seek pleasure and enjoyment and if the marriage life can no longer provide what they are looking for then they will choose to divorce. This creates the erosion of the sacredness of the institution of marriage so that divorce becomes commonplaceh, and the second. The complete breakdown of the family system, the focus of parents is no longer on the Household even though for different reasons. The waning of local wisdom, for example, was once a complete mother at home and was able to pay attention to children but now they work outside the home to promote gender equality and women's rights deficits, the waning of conflict resolution cultures such as families and relatives capable of mediating conflict occurs to their children, but today many have faded, for reasons of domestic affairs let alone solved, they have grown up etc., resulting in tension and crisis in the family and lead to divorce.